2014
DOI: 10.1159/000360141
|View full text |Cite
|
Sign up to set email alerts
|

Kidney Protection against Ischemia/Reperfusion Injury by Myofibrillogenesis Regulator-1

Abstract: Background/Aims: Ischemia/reperfusion (I/R) injury is characterized by cytoskeletal reorganization and loss of polarity in proximal tubule epithelial cells. Previously, we showed that myofibrillogenesis regulator (MR)-1 promoted actin organization in cardiomyocytes. MR-1 is also expressed in the kidney. Methods: In this study, we investigated MR-1 expression in acute renal failure induced by I/R in Sprague-Dawley rats. We determined the MR-1 expression and the ratio of fibrous actin (F-actin) to globular actin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 44 publications
2
5
0
1
Order By: Relevance
“…In addition, MR-1 also induced MLC-2 expression, which further increased MLC-2 total phosphorylation. When combined with our previous study that showed MR-1 interacted directly with MLC-2, and MLC-2 was critical for actin polymerization to form F-actin [23] and regulated by MLCK [13], these data demonstrate that MR-1 protects cardiomyocytes from H/R injury by attenuating damage of actin filaments and activating the MLCK/MLC-2 pathway.…”
Section: Discussionsupporting
confidence: 72%
See 4 more Smart Citations
“…In addition, MR-1 also induced MLC-2 expression, which further increased MLC-2 total phosphorylation. When combined with our previous study that showed MR-1 interacted directly with MLC-2, and MLC-2 was critical for actin polymerization to form F-actin [23] and regulated by MLCK [13], these data demonstrate that MR-1 protects cardiomyocytes from H/R injury by attenuating damage of actin filaments and activating the MLCK/MLC-2 pathway.…”
Section: Discussionsupporting
confidence: 72%
“…Our previous studies showed that MR-1 interacted directly with MLC-2 and induced cardiomyocyte hypertrophy via sarcomere organization [8]. MR-1 overexpression promoted actin polarity through the MLC-2-mediated reorganization of actin filaments and protected HK-2 cells from H/R injury [13]. This further suggests that MR-1 might protect cells from H/R injury through attenuating H/R-induced damage of the actin filament.…”
Section: Introductionmentioning
confidence: 82%
See 3 more Smart Citations